A modern Green Revolution gene for reduced height in wheat. (10th November 2017) - Würschum, Tobias; Langer, Simon M.; Longin, C. Friedrich H.; Tucker, Matthew R.; Leiser, Willmar L.
Summary: Increases in the yield of wheat during the Green Revolution of the late 20 th century were achieved through the introduction of Reduced height ( Rht ) dwarfing genes. The Rht‐B1 and Rht‐D1 loci ensured short stature by limiting the response to the growth‐promoting hormone gibberellin, and are now widespread through international breeding programs. Despite this advantage, interference with the plant's response to gibberellin also triggers adverse effects for a range of important agronomic traits, and consequently modern Green Revolution genes are urgently required. In this study, we revisited the genetic control of wheat height using an association mapping approach and a large panel of 1110 worldwide winter wheat cultivars. This led to the identification of a major Rht locus on chromosome 6A, Rht24, which substantially reduces plant height alone as well as in combination with Rht‐1b alleles. Remarkably, behind Rht‐D1, Rht24 was the second most important locus for reduced height, explaining 15.0% of the genotypic variance and exerting an allele substitution effect of –8.8 cm. Unlike the two Rht‐1b alleles, plants carrying Rht24 remain sensitive to gibberellic acid treatment. Rht24 appears in breeding programs from all countries of origin investigated, with increased frequency over the last decades, indicating that wheat breeders have actively selected for this locus. Taken together, this study reveals Rht24 as an important Rht gene of commercial relevance in worldwide wheat breeding. Significance Statement: Reduced height ( Rht ) loci were the basis of the Green Revolution and the Rht‐B1 and Rht‐D1 semi‐dwarfing genes are now utilized globally for wheat breeding. Here, we characterize the novel Rht24 locus, show that Rht24 is of worldwide relevance and that it may be a better Green Revolution gene than those originally employed.